2019
DOI: 10.1590/1980-5373-mr-2018-0466
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Warm Rolling on the Corrosion and Mechanical Properties of UNS S32205 Duplex Stainless Steel

Abstract: Duplex stainless steel (DSS) has been considered as an excellent alternative for applications where high corrosion resistance and high mechanical strength are required. Therefore, microstructure and properties of DSS remain topics of much interest. For this purpose, the effect of warm-rolling was studied in a duplex stainless steel. The focus of this work was 2205 which is one of the most useful type of DSS. Although evolution of microstructure, texture and tensile properties during warm rolling of DDS have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…It has been reported that the change in the value of Q for the passive layer is an indicator of a change in the thickness of the passive film. [ 42 ] The passive layer thickness is inversely proportional to Q . [ 43 ] Thus, the base metal passive layer thickness was the highest, and it was adversely affected by both EB and GTA welding.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the change in the value of Q for the passive layer is an indicator of a change in the thickness of the passive film. [ 42 ] The passive layer thickness is inversely proportional to Q . [ 43 ] Thus, the base metal passive layer thickness was the highest, and it was adversely affected by both EB and GTA welding.…”
Section: Resultsmentioning
confidence: 99%
“…A thicker passive film layer provides more effective protection against corrosion for similar chemical composition. [ 42 ] The magnitude of parameter “ n ” represents the corrosion process on the surface of the test specimen. The smaller the value, the greater the surface heterogeneity.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have been performed about microstructural and metalurgical aspects of these alloys (weldability, aging, heat treatments, phases, etc. for instance see [2][3][4][5][6][7][8][9][10][11][12] , but only a few about the phenomenological aspects of the macrossopic mechanical behavior, mainly concerned with Finite Element simulations 9,10 . It is not the goal of the present paper to perform an extensive review of these studies, but the previously mentioned references give a reasonable idea of the research in thie area.…”
Section: Introductionmentioning
confidence: 99%